The Role of Social Media in Legal Practice in Nigeria - Omoleke , Muslim (ABUAD Law Journal, 2025)
Social media has significantly impacted legal practice in Nigeria, reshaping how legal professionals interact with clients, manage their practices, and engage with the broader community. This digital transformation offers substantial benefits, including enhanced visibility for legal practitioners, increased client outreach, and a platform for sharing legal insights and updates. Social media platforms such as LinkedIn, Twitter, and Facebook provide lawyers with tools to establish their expertise, build professional networks, and participate in legal discussions, thus fostering greater public awareness of legal issues. However, the integration of social media into legal practice also presents challenges, including concerns about maintaining client confidentiality, adhering to ethical standards, and managing the accuracy of information shared. Nigerian legal practitioners must navigate these challenges by implementing clear social media policies, investing in digital literacy, and ensuring compliance with regulatory and ethical guidelines. This paper is geared towards balancing the opportunities and risks associated with social media as it is crucial for leveraging its potential to enhance legal practice while safeguarding professional integrity. It also explores the essentiality for legal professionals in Nigeria to stay abreast of technological advancements and regulatory developments to maximize the benefits and mitigate potential drawbacks. This paper adopts a doctrinal research methodology through a review of existing literature. The findings reveal a growing reliance on social media among Nigerian legal professionals, albeit with limited awareness of potential ethical pitfalls. The paper recommends that legal practitioners develop comprehensive social media strategies and receive continuous training on digital best practices to harness its benefits while maintaining professional integrity.